Achievement Gaps by Migration Background and the Role of Early Childhood Education and Care: Evidence from a Nationally Representative Irish Cohort Study - Sprong, Stefanie Lola (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2023)
Drawing on the longitudinal data from the Growing Up in Ireland (GUI) '08 Cohort, this thesis sets out to contribute to the literature on the academic achievement of children with a migration background and Early Childhood Education and Care (ECEC). The first part of the thesis, constituted of papers one and two, sheds light on educational inequalities by migration background during early and middle childhood. The second part, made up by papers three and four, explores if ECEC could potentially serve as an equaliser to reduce existing achievement gaps by migration background. The results indicate that Irish children of migrant origin may not have equal opportunities at the start of life and that ECEC could provide part of the answer to the question of how to foster their integration.
APPROVED
Keywords: Academic Achievement; Educational inequality; Achievement gaps; English language; Migration background; Early Childhood Education and Care; Children of migrant origin; GUI '08; Quantitative; Longitudinal data; Growing Up in Ireland